Technology for Justice: How Information Technology Can Support Judicial Reform - Dory Reiling (My University, 2016)
This is a study that addresses the implications of utilizing information technology in court systems at a national and international level. It focuses mainly on the implications in the arenas of case delay, access to justice, and impartiality, integrity, and corruption.